Anderson in bloom : a novel - Dugan, Jennifer (Avon, 2026)
Former child star Anderson "Andy" Ducharme is hiding--has been for a long time, if she's honest with herself, which she isn't. When she suddenly cut off all ties and left LA six years earlier to work in a flower shop in coastal New England, she wasn't just running away from toxic relationships, embezzling agents, and all the rest of her Hollywood life; she was running to something... sort of, if you squinted, and if you accepted that what she was running toward was little more than a vacation daydream she had made up with her (in)famous ex, and former costar, Nicole "Nikki" Price. Then Nikki announces her plan to write a tell-all book about growing up in Hollywood and their tumultuous time on the Nik and Andy show, and Andy's feelings of hurt and betrayal come rushing back. Emboldened by anger (and maybe one too many drinks), Andy does something very stupid: she texts her ex for the first time in years. No one's more shocked than Andy when Nikki actually shows up to her small florist shop, looking for answers. Andy is fully prepared to send Nikki away, but it seems Nikki has some unfinished business as well. Now that she finally knows where Andy's been hiding, she's not letting her go so easy. And with each passing encounter, Andy can't deny the simmering physical attraction that threatens to boil over every time they get close. But can the two of them really reunite without wrecking Andy's carefully rebuilt life? Or is she setting herself up for a fresh heartbreak?